Lili inventa o mundo onde não falta poesia: a mediação da leitura literária nas séries iniciais do ensino fundamental - Souza, Andréa Alves da Silva (2015)
This dissertation aims to analyze and discuss the mediation process of literary reading, with an emphasis on poetry reading, within the family context and at school. It is intended to be investigated whether children who enter the first grade of elementary school, whit more systematic practices of literary reading with and within family, are able to have better reading skills at school. Based on authors like Azevedo (2004 e 2005), Bakhtin (2003 e 2006), Candido (2004), Cosson (2014), Faria (2004), Souza (2004), Spiegel (2001), Vygotsky (1987), Zilberman (1986 e 1987), Huizinga (2012) and others, this research initially presents a reflection on the formation of literary readers and the reading mediation to demonstrate how literary reading favors the child’s transit through the world of invention and fantasy. This process not only results in creative, cognitive, social, and cultural development but also contributes to a more humanized education. In sequence, it is discussed the role of poetry in the construction of the children’s universe of play. Therefore, the books Lili inventa o mundo, Sapato furado and O sapo amarelo, written by Mario Quintana, but these last two used as supplements, were selected as the corpus of analysis of this dissertation. The main goal is to demonstrate how the world of play, fantasy and imagination presented by the poems, effectively contributes to the formation of the child as a reader. Associated with this, some research tools, such as the questionnaire and the interview, were applied. In addition to these, some actions were performed, as part of a field research, as a way to debate how family and school’s mediation (in the early grades) contributes to the child’s education as a reader. The results indicate the importance of the family as the first mediator in the reader’s education process and the continuity of this mediation in the early stages of schooling. However, it is also evident that the school environment is the main guide of the education process of the literary reader, especially the poetry reader. It is believed that the work with this text genre with the student inside classroom can overcome the stage of schooling and allow the adult to keep reading. After all, the teacher is also provocative, conductor of paths for reading, so that the child can, in another phase, venture out alone.